Introducing an Advance Tax Ruling (ATR) Regime - Waerzeggers, Christophe (Tax Law Technical Note; Tax Law Technical Note ;, 2016)
Advance tax rulings are a common feature of mature tax systems. The tax systems of the United States, the United Kingdom, the Netherlands, Germany, Australia, and South Africa all have established ruling practices. Taxpayers can obtain an advance tax ruling in nearly all OECD member countries. Increasingly, many non-OECD countries are also offering advance tax rulings. An advance tax ruling regime seeks to promote clarity and consistency regarding the application of the tax law for both taxpayers and the tax authority. However, there are also inherent risks associated with the proliferation of granting confidential advance tax rulings which are not published or otherwise reported. This Tax Law IMF Technical Note focuses on designing an advance tax ruling regime in the nature of private tax rulings.